Account of 'The Dane's Dyke,' an ancient Camp at Fife-Ness (Proceedings of the Society of Antiquaries of Scotland, 1862)
The article begins with accounts of the death of King Constantine II in Fife, although the author is hesitant to conclude that the king was murdered in "Constantine's Cave" based on the available evidence. The author then goes on to describe a survey of the Danes Dyke, a fortification nearby this cave, which he argues was occupied by the Danish and Norwegian forces for a considerable time before the battle in which Constantine was killed.Following this paper is a summary of the exhibition of two original Robert Burns manuscripts by fellows. Meeting notes for 16 March, 1859 are appended.